2013
DOI: 10.1002/phar.1299
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Proton Pump Inhibitors in the Management of Pediatric Gastroesophageal Reflux Disease

Abstract: Proton pump inhibitors (PPIs) are commonly prescribed to infants and children for managing gastroesophageal reflux disease (GERD). Recently published literature illustrates conflicting evidence on the efficacy of PPIs in infants and children. Randomized controlled trials and systematic reviews have demonstrated a lack of efficacy of PPIs, specifically in young infants. Furthermore, emerging evidence also suggests that PPIs are not as benign as once thought, with newer data implicating a potential association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Rebound acid hypersecretion after the discontinuation of proton pump inhibitor has been reported to be a factor affecting the pH. 32 In the present study, four patients received proton pump inhibitors before stopping the medication, while 21 did not. No significant difference was observed between these 2 groups with regard to the percentage of time for which the gastric pH was < 4 (P = 0.972).…”
Section: Discussionmentioning
confidence: 59%
“…Rebound acid hypersecretion after the discontinuation of proton pump inhibitor has been reported to be a factor affecting the pH. 32 In the present study, four patients received proton pump inhibitors before stopping the medication, while 21 did not. No significant difference was observed between these 2 groups with regard to the percentage of time for which the gastric pH was < 4 (P = 0.972).…”
Section: Discussionmentioning
confidence: 59%
“…The case–control study of 68 children with CDI by Turco et al 24 also showed a significantly higher rate of PPI use in those cases with CDI. However, the fact that the group of CDI cases in that study had a higher proportion of children with inflammatory bowel disease than the control group is considered a major limitation 8. The study by Brown et al 25 did not show an increased CDI risk in children receiving PPIs, whereas a 4.5 times greater CDI risk was shown in children receiving H2RAs when compared with those not receiving acid-suppressive therapy.…”
Section: Toxicity Profiles Of Ppi In Childrenmentioning
confidence: 78%
“…Furthermore, this Cochrane review found no trials addressing the effectiveness of pro-motility agents such as domperidone. Second, an emerging body of evidence from observational studies have reported on the potential harms of these medications (10,11). These studies have shown an increased risk of infections such as pneumonia and gastroenteritis in children on PPIs and H2Ras (10,11,12).…”
Section: Expert Commentarymentioning
confidence: 99%